UJI TOKSISITAS SUBLETAL EFLUEN INDUSTRI MENGGUNAKAN IKAN NILA (Oreochromis niloticus) SEBAGAI ALAT PEMANTAUAN BIOLOGIS - Atiek Moesriati (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2004)
The gills of nila fish which was exposed to the effluent of copper smelter and surfactant plants showed 100% hyperplasia. Whereas the effluent of paper plant caused 79,13% hyperplasia on lamella branchialis. The effluent concentration of copper smelter plant which gave significant influence of respiration rate was 40% volume with TDS, TSS, Fe, Zn, Cd, Pb, F concentrations of 1.590 mg/l, 27 mg/l, 0,39 mg/l, 0,116 mg/l, 0,12 mg/l, 0,048 mg/l and 0,044 mg/l respectively. Surfactant plant effluent that caused significant influence of respiration rate was 60% volume with BOD, COD, TSS, MBAS concentrations of 2,4 mg/l, 17,76 mg/l, 31,2 mg/l, and 0,6 mg/l respectively.